2010
DOI: 10.1021/nn101451q
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-induced Electromagnetic Coupling in Gold/Polymer Hybrid Plasmonic Structures Probed by Surface-Enhanced Raman Scattering

Abstract: This paper describes a general stepwise strategy combining diazonium salt, surface-initiated atom transfer radical polymerization (SI-ATRP), and click chemistry for an efficient gold surface functionalization by poly(N-isopropylacrylamide) (PNIPAM) brushes and gold nanoparticle assemblies. We designed by this way a new plasmonic device made of gold nanoparticles separated from a gold film through a thermoresponsive polymer layer. This organic layer responds to temperature variations by conformational changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 66 publications
(81 reference statements)
2
107
0
Order By: Relevance
“…This led to shrinkage of the interparticle spacing to a size suitable for generation of more effective SERS hot spots. Further evidence of the contribution of the shrinkage came from temperature-and pH-induced formation of reversible hot spots [28][29][30][31]. In the present study, a similar change in SERS effect was observed, i.e., the SERS signal was very weak at the beginning of introduction of an external magnetic field, reaching maximum intensity after 5 s, and became stable thereafter.…”
Section: Magnetic Tuning Sers Of Fe 3 O 4 @Au Monolayer Filmsupporting
confidence: 84%
See 2 more Smart Citations
“…This led to shrinkage of the interparticle spacing to a size suitable for generation of more effective SERS hot spots. Further evidence of the contribution of the shrinkage came from temperature-and pH-induced formation of reversible hot spots [28][29][30][31]. In the present study, a similar change in SERS effect was observed, i.e., the SERS signal was very weak at the beginning of introduction of an external magnetic field, reaching maximum intensity after 5 s, and became stable thereafter.…”
Section: Magnetic Tuning Sers Of Fe 3 O 4 @Au Monolayer Filmsupporting
confidence: 84%
“…Wang et al developed approaches to accomplish the dynamic assembly of nanostructures for controlling optical, electronic, and magnetic properties [27]. In other studies, the interparticle spacing was dynamically controlled using nanoparticles decorated with temperature-responsive polymer as a substrate [28][29][30]. Lu et al fabricated a nanoparticle monolayer film through the LangmuirBlodgett approach and transferred it to a temperature-responsive polymer substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the probability to check the interaction between Au or Ag NPs on the polymer layer to optimize the Raman increment factor, for instance, via the use of polymer films of different thickneses [6][7][8]. Recently, pH and thermally switchable systems made of Agadsorbed hydrogels or layer-by-layer films and core-shell NPs coated with poly(Nisopropylacrylamide) were used for SERS applications having dynamically control the distance between Au or Ag NPs and the molecular probes on flat Au surface [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…If these radicals are present during the synthesis of Fe 3 O 4 NPs, these aryl radicals form NPs modified with aryl groups through covalent linkages affording to a highly stable anchoring of the organic coating at the surface of the NPs. Diazonium salts have been widely used as coupling agents for the grafting of polymer coatings upon carbon-based 28 and metallic 29 (platinum, ruthenium, palladium, gold and titanium) planar and/or NP surfaces, affording strong linkages.…”
Section: Introductionmentioning
confidence: 99%